2009
DOI: 10.1093/nar/gkp697
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary network in mammalian mitochondrial tRNAAsp revealed by solution probing and phylogeny

Abstract: Primary and secondary structures of mammalian mitochondrial (mt) tRNAs are divergent from canonical tRNA structures due to highly skewed nucleotide content and large size variability of D- and T-loops. The nonconservation of nucleotides involved in the expected network of tertiary interactions calls into question the rules governing a functional L-shaped three-dimensional (3D) structure. Here, we report the solution structure of human mt-tRNAAsp in its native post-transcriptionally modified form and as an in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 73 publications
3
28
0
Order By: Relevance
“…In addition to that, this change could also alter the folding of the tRNA. In bacterial, archaeal and eukaryotic cytosolic tRNAs, the transition from the secondary (cloverleaf) to the tertiary (L-shape) structures is supported by nine interactions involving conserved and semiconserved residues located in the D and T-loops and the core of the molecule (Messmer et al, 2009). The hydrogen bonds between the nucleotides 12 (corresponding to 5644A in mt-tRNA Ala ) and 23 (5636T) participate in this folding; therefore, the loss of these hydrogen bonds might compromise the tertiary structure of the molecule.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to that, this change could also alter the folding of the tRNA. In bacterial, archaeal and eukaryotic cytosolic tRNAs, the transition from the secondary (cloverleaf) to the tertiary (L-shape) structures is supported by nine interactions involving conserved and semiconserved residues located in the D and T-loops and the core of the molecule (Messmer et al, 2009). The hydrogen bonds between the nucleotides 12 (corresponding to 5644A in mt-tRNA Ala ) and 23 (5636T) participate in this folding; therefore, the loss of these hydrogen bonds might compromise the tertiary structure of the molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Then they are chemically modified to ensure their proper folding, recognition, and basepairing (Helm and Attardi, 2004;Messmer et al, 2009). Modifications of the anticodon stem, such as the hypermodified nucleoside 5-methylaminomethyl-2-thiouridylate at position 34, create the "wobble-base" necessary to enable the recognition of multiple codons (Agris et al, 2007).…”
Section: Transcriptomementioning
confidence: 99%
“…The 3D structure of canonical tRNAs is based on a set of tertiary interactions between nucleotides at distance in the secondary structure, in particular on a network of interactions defining and stabilizing the "central core" of the L-shaped structure. Fine-tuned chemical structural probing on two case studies, human mt-tRNA Asp and bovine mt-tRNA Phe confirmed the existence of these networks (Messmer et al 2009;Wakita et al 1994). It remains to be verified if such networks can take place in all mt-tRNAs, an hypothesis that could not be supported by nucleotide conservation, but that will need a more detailed consideration of nucleotide partnership rules as tackled by Leontis and Westhof (Leontis et al 2002).…”
Section: Structural Properties Of Mammalian Mitochondrial Trnasmentioning
confidence: 88%
“…It remains to be verified if such networks can take place in all mt-tRNAs, an hypothesis that could not be supported by nucleotide conservation, but that will need a more detailed consideration of nucleotide partnership rules as tackled by Leontis and Westhof (Leontis et al 2002). Initial data are available suggesting that at least all mammalian mt-tRNA Asp would benefit from the set of tertiary network interactions despite nonconservation of involved nucleotides (Messmer et al 2009). Extension of the analysis to the full set of mammalian mt-tRNAs is in progress.…”
Section: Structural Properties Of Mammalian Mitochondrial Trnasmentioning
confidence: 99%
See 1 more Smart Citation